Justification and critique towards a critical theory of politics - Forst, Rainer (Polity Press, 2014)
Rainer Forst develops a critical theory capable of deciphering the deficits and potentials inherent in contemporary political reality. This calls for a perspective which is immanent to social and political practices and at the same time transcends them. Forst regards society as a whole as an "order of justification" comprising complexes of different norms referring to institutions and corresponding practices of justification. The task of a "critique of relations of justification", therefore, is to analyse such legitimations with regard to their validity and genesis and to explore the social and political asymmetries leading to inequalities in the "justification power" which enables persons or groups to contest given justifications and to create new ones. -- Publisher description.